ANALISIS PENGARUH DISIPLIN, MOTIVASI, KOMPETENSI DAN KEPEMIMPINAN, TERHADAP KINERJA SERTA DAMPAKNYA PADA PRESTASI KERJA DAN KEPUASAN KERJA - Evisastra Evisastra; Erwin Masud; Suhardi Suhardi (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to analyze and find out how much influence Discipline, Motivation, and competence and leadership on employee performance in the Public Works Office of South Bangka Regency and its impact on work performance and employee job satisfaction. This research is a quantitative descriptive study with a total sample of 63 respondents while the sampling method used in this study is saturated sampling method. The results showed that the variables of discipline, motivation, competence, and leadership had a significant effect on the performance of employees in the Public Works Office of South Bangka Regency. Leadership in this study has the highest influence on employee performance while motivation variables are variables that have the least influence on employee performance. For further research can examine the influence of discipline, motivation, competence, and leadership on performance by adding other relevant contingency variables and with the object of expanded research.